Effects of sodium lauryl sulfate and postbiotic toothpaste on oral microecology - Shi, Qingying; Sun, Lianlian; Gao, Jing; Li, Fengzhu; Chen, Dongxiao; Shi, Tingting; Tan, Youlan; Chang, Huimin; Liu, Xiaozhi; Kang, Jian; Lu, Fuping; Huang, Zhengmei; et al. (Journal of oral microbiology, 2024)
The diversity and delicate balance of the oral microbiome contribute to oral health, with its disruption leading to oral and systemic diseases. Toothpaste includes elements like traditional additives such as sodium lauryl sulfate (SLS) as well as novel postbiotics derived from probiotics, which are commonly employed for maintaining oral hygiene and a healthy oral cavity. However, the response of the oral microbiota to these treatments remains poorly understood. In this study, we systematically investigated the impact of SLS, and toothpaste containing postbiotics (hereafter, postbiotic toothpaste) across three systems: biofilms, animal models, and clinical populations. SLS was found to kill bacteria in both preformed biofilms (mature biofilms) and developing biofilms (immature biofilms), and disturbed the microbial community structure by increasing the number of pathogenic bacteria. SLS also destroyed periodontal tissue, promoted alveolar bone resorption, and enhanced the extent of inflammatory response level. The postbiotic toothpaste favored bacterial homeostasis and the normal development of the two types of biofilms , and attenuated periodontitis and gingivitis via modulation of oral microecology. Importantly, the postbiotic toothpaste mitigated the adverse effects of SLS when used in combination, both and . Overall, the findings of this study describe the impact of toothpaste components on oral microflora and stress the necessity for obtaining a comprehensive understanding of oral microbial ecology by considering multiple aspects.